2019
DOI: 10.1021/acs.joc.9b01650
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Ring C Pyrrole of Native Chlorophylls and Bacteriochlorophylls

Abstract: As part of a program to develop practical syntheses of members of the family of (bacterio)­chlorophylls, two routes to 2-iodo-3-methyl-4-(3-methoxy-1,3-dioxopropyl)­pyrrole, a precursor of the universal ring C, have been developed. The β-ketoester of ring C is expected to give rise to ring E upon Knoevenagel condensation and Nazarov cyclization with a ring D constituent as demonstrated in an analogue synthesis. Two viable routes were developed beginning with N-TIPS-pyrrole or with 4-oxo-2-pentene and TosMIC, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…S6) allowed identification of 3-acetyl-4-methylpyrrole for the compound at 16.05 min. All of these data are in accordance with the literature ( 33 35 ). Thus, deletion of PaNsdD in both wild-type and ΔPaStcA background almost completely blocked the production of 3-acetyl-4-methylpyrrole (at 16.05 min), implying that PaNsdD positively regulates its biosynthesis.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S6) allowed identification of 3-acetyl-4-methylpyrrole for the compound at 16.05 min. All of these data are in accordance with the literature ( 33 35 ). Thus, deletion of PaNsdD in both wild-type and ΔPaStcA background almost completely blocked the production of 3-acetyl-4-methylpyrrole (at 16.05 min), implying that PaNsdD positively regulates its biosynthesis.…”
Section: Resultssupporting
confidence: 92%
“…Fractions containing the products were pooled, and the mobile phase was evaporated under reduced pressure to furnish 1.9 mg of the desired pure compound. NMR and MS data of this metabolite were in accordance with the literature ( 33 , 34 ) and were permitted to identify the product as 3-acetyl-4-methylpyrrole.…”
Section: Methodsmentioning
confidence: 63%
“…The organic extract was dried (Na 2 SO 4 ) and concentrated to a yellow oil. Chromatography [silica, hexanes/ethyl acetate (3:1) to ethyl acetate] afforded a colorless oil (13.2 g, 35%): 1 tert-Butyl (4-Nitrophenyl)glutarate (8). A solution of 7 (8.46 g, 45.0 mmol) in anhydrous THF (135 mL) was treated with 4nitrophenol (6.88 g, 49.5 mmol) and DCC (13.9 g, 67.5 mmol) under argon at 0 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…A current objective is to adapt the general synthesis to accommodate the substituents characteristic of the native macrocycles. To date, we have synthesized the ring C pyrrole, 8 shown that stereodefined model substituents (17-methyl, 18-ethyl) in ring D can be incorporated at an early stage of the synthesis and carried through Knoevenagel and double-ring closure processes to form the macrocycle without loss of stereochemical integrity, 9 refined the conditions for the double-ring closure, 10 compounds containing a 3-acetyl as well as other substituents. 11 The prior incorporation of an acetyl 11 or carboethoxy 9,10 group at the 3-position in each case required independent synthesis beginning with the corresponding substituted pyrrole.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pyrroles, π-excess N-heterocyclic systems, are found in nature, and several derivatives with interesting properties have been synthesized [1][2][3][4][5]. Because of the importance of pyrrole and its substituted derivatives as basic substructures in natural and synthetic products, the synthesis of these five-membered heterocycles is of interest to researchers.…”
Section: Introductionmentioning
confidence: 99%